Entre memórias, jongos e cultura material: por uma etnografia arqueológica na Fazenda do Colégio, Campos-RJ - Fernando Silva Myashita (2017)
In this research I investigate the ways in which ex-dwellers of the village area in the Fazenda do Colégio estate assign values and meanings to the materiality of the place. Beyond the architectonic value of the estates main building (Solar do Colégio), which is listed by the National Heritage, these interlocutors suggest the areas of archaeological interest also have other layers of meaning, determined by ancestral and affective links. Following the approach named by some authors as archaeological ethnography, I explore how the excavations stimulated ex-dwellers to talk about their memories of the past and of daily practices connected to the village. Based on other kinds of evidences I also investigate the long duration processes that influenced the formation of a community descended from the slave quarters (senzala) of the Fazenda do Colégio estate. It is usually imagined that such community originated the population of the estate village. I discuss the limits and possibilities of an archaeology of the villages recent past and its relation with the slave quarters archaeological past.